Beyond checkpoint inhibition: PD-1 cis-targeting of an IL-2Rβγ-biased interleukin-2 variant as a novel approach to build on checkpoint inhibition. (31st December 2023) - Codarri Deak, Laura; Hashimoto, Masao; Umaña, Pablo; Klein, Christian
ABSTRACT: The immunocytokine PD1-IL2v was designed to overcome liabilities and improve efficacy of IL-2 therapies. PD1-IL2v preferentially targets PD-1 + T-cells and acts on antigen-specific stem-like PD-1 + TCF-1 + CD8 + T-cells expanding and differentiating them towards better effectors resulting in superior efficacy in LCMV chronic infection and tumor models compared to checkpoint inhibition.